2012
DOI: 10.5897/ajps12.132
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutritional media and photoperiods on in vitro asymbiotic seed germination and seedling development of Dendrobium aqueum Lindley

Abstract: Dendrobium aqueum Lindley is an epiphytic orchid decreasing in nature owing to environmental disturbance and inherent lower germination rates of mature seeds. To conserve this species, in vitro asymbiotic media and photoperiod screening were experimented. Twenty asymbiotic orchid seed germination media were examined to get the optimal medium for germination and seedling development under 16/8 hrs photoperiod. Highest seed germination occurred in 1 / 2 MS medium (93.41%) followed by mMS (91.04%) and m ½ MS (90.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
1
14
1
Order By: Relevance
“…Parthibhan et al 2012). a Imbibed, enlarged seeds (zygotic embryos) with testa, turned into green (photosynthetic) 920 after 15 days of culture.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 93%
See 3 more Smart Citations
“…Parthibhan et al 2012). a Imbibed, enlarged seeds (zygotic embryos) with testa, turned into green (photosynthetic) 920 after 15 days of culture.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 93%
“…However, green pod culture or immature seed germination involves the use of green, undehisced capsules, which are harvested 70 days after pollination, opened and seeds are inoculated on culture media (Soundararajan 2009; Table 1). The time required for seed germination ranges from 30 to 59 days (Alam et al 2002;Sunitibala and Kishor 2009;Parthibhan et al 2012). Green pod seeds grown on Robert Ernst medium (Ernst 1982), KP medium (Knop 1865), KC medium, Curtis medium (Curtis 1936) and Pfeffer (Harvais 1972) medium became pale green or whitish green and eventually produced weak seedlings but on VW medium, KC medium, Thomale GD medium (Thomale 1954), Mitra et al medium (Mitra et al 1976) and Wolter and Skoog medium (WS; Wolter 1968) the seeds became brown and could not germinate.…”
Section: Explant Agementioning
confidence: 99%
See 2 more Smart Citations
“…Comparative results were found with Calopogon tuberosus, where seeds at an advanced stage (Stage 6) were only observed under light incubation (Kauth et al, 2006). Similarly, although light was not a limiting factor for early stages of seed germination, it was essential for subsequent seedling development in Dendrobium aqueum (Parthibhan et al, 2012). The authors observed that the 0/24-h light/dark photoperiod supported seeds up to the protocorm stage with poor seedling growth; seedling development occurred only when longer photoperiods were used.…”
Section: Discussionmentioning
confidence: 72%